Principles of Coding and Reimbursement for Surgeons - Savarise, Mark; Senkowski, Christopher (Springer International Publishing : Imprint: Springer, 2017)
This text provides the in-depth understanding of the mechanisms that guide coding and reimbursement. The text is meant to be useful to surgeons in practice, both in general surgery and in surgical subspecialties; practice management teams of surgical practices and to resident physicians in surgery. Part 1 of the text addresses the CPT coding process, the relative valuation system (RVU), the ICD-9 and ICD-10 systems of classification, Medicare Part B payment rules for physicians, the DRG system and Medicare Part A payment for hospitals, alternative payment models, and the myriad of quality measures of importance to surgeons. Part 2 of the text addresses specific coding in areas where surgeons historically have had the most difficulty. This is not meant to substitute for the available texts, software or courses on coding, but to provide the historical background and rationale for the specific coding rules. Principles of Coding and Reimbursement for Surgeons will be of great value to general surgeons and surgical subspecialists in private practice, academic institutions, and employed positions. It will provide direction to management teams from practice and institutional levels. It is also of use to surgical trainees and to researchers in health policy issues.